Surgical intervention for patients with rheumatoid arthritis is declining except for foot and ankle surgery: A single-centre, 20-year observational cohort study. Issue 3 (10th May 2022) - Tominaga, Ayako; Ikari, Katsunori; Yano, Koichiro; Tanaka, Eiichi; Inoue, Eisuke; Harigai, Masayoshi; Okazaki, Ken
ABSTRACT: Objectives: A global downward trend in the number of rheumatoid arthritis (RA)-related surgeries has been reported. The purpose of our study was to investigate the latest trends in RA-related surgeries in a single-centre Japanese RA cohort. Methods: This study was a retrospective analysis of RA-related surgeries between 2001 and 2020 in the Institute of Rheumatology Rheumatoid Arthritis cohort. An average of 4944 patients per semi-annual survey was included in the study. The primary goal was to analyse the half-year period prevalence proportion (HPP) of RA-related surgeries in a 20-year period, and the secondary goal was to analyse the HPP of surgeries by site or by categories of disease activity. Results: There has been a downward trend in the HPP of RA-related surgeries in the 20-year study period. The total HPP of RA-related surgeries decreased by 50.3% during the 20-year study period. There was a significant decrease in knee, hip, shoulder/elbow, and hand procedures. Only foot/ankle joint surgeries significantly increased in volume during this period ( p = .001). The HPP of RA-related surgeries remained unchanged in patients with remission or low disease activity. Conclusions: The number of RA-related surgeries decreased over a 20-year period, but foot/ankle joint surgeries increased in the site-specific evaluation.